Learning Habits As Factors Influencing Academic Performance in Medical Students - Sajida Agha, Ata ur Rehman (Pakistan Journal of Psychology, 2016)
The objectives of the study were multifaceted: first, to explore the various learning habits preferred by medical students; second, to examine the predictive association between various learning habits and academic performance; third, to examine the age-wise, gender-wise, and education level-wise (i.e. pre-clinical and clinical) differences on learning habits. The sample comprised of 361 medical students of King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) with an age range of 17-28 years. The results indicated that most commonly used learning habit by medical students were motivation and metacognition and self-regulation. Further, learning habits of motivation, test taking anxiety and metacognition and selfregulation are seen as significant predictors of academic performance. Moreover, age-wise and education-level wise differences are evident only on metacognition and selfregulation whereas gender-wise differences are found on information processing learning habits. It is concluded that factors of learning habits can increase the students’ performance in the examination.